Cultural Approaches in Digital Health Promotion: A Strategic Conceptual Framework - Dewi, Riskha Dora Candra (Strata International Journal of Social Issues, 2025)
Digital health promotion has become a promising tool for improving public health. However, its success largely depends on the appropriate cultural approach in delivering health messages. This study aims to analyze the effectiveness of cultural approaches in digital health promotion and identify suitable health message adaptation strategies for various social and cultural contexts. Using a qualitative research method with a literature review approach, the findings of this study indicate that cultural approaches play a crucial role in enhancing public engagement with technology-based health programs. Adaptation strategies such as community participation, the use of cultural brokers, narrative-based approaches, and the application of social and behavioral theories have proven effective in aligning health communication with the values and social norms of target populations. Therefore, integrating cultural approaches into digital health promotion is recommended to improve the effectiveness of interventions, particularly in culturally diverse countries such as Indonesia. Additionally, leveraging artificial intelligence and data analytics can serve as a solution for identifying cultural preferences and developing more inclusive and sustainable health communication strategies.